Assessment of the effects of cannabidiol and a CBD-rich hemp extract in Caenorhabditis elegans - Camacho, Jessica A.; Welch, Bonnie; Ferguson, Martine; Sepehr, Estatira; Vaught, Cory; Zhao, Yang; Fitzpatrick, Suzanne; Yourick, Jeffrey; Sprando, Robert L.; Hunt, Piper Reid (Frontiers in Toxicology, 2024)
Consumer use of cannabidiol (CBD) is growing, but there are still data gaps regarding its possible adverse effects on reproduction and development. Multiple pathways and signaling cascades involved in organismal development and neuronal function, including endocannabinoid synthesis and signaling systems, are well conserved across phyla, suggesting that Caenorhabditis elegans can model the in vivo effects of exogenous cannabinoids. The effects in C. elegans on oxidative stress response (OxStrR), developmental timing, juvenile and adult spontaneous locomotor activity, reproductive output, and organismal CBD concentrations were assessed after exposure to purified CBD or a hemp extract suspended in 0.5% sesame oil emulsions. In C. elegans, this emulsion vehicle is equivalent to a high-fat diet (HFD). As in mammals, HFD was associated with oxidative-stress-related gene expression in C. elegans adults. CBD reduced HFD-induced OxStrR in transgenic adults and counteracted the hypoactivity observed in HFD-exposed wild-type adults. In C. elegans exposed to CBD from the onset of feeding, delays in later milestone acquisition were irreversible, while later juvenile locomotor activity effects were reversible after the removal of CBD exposure. CBD-induced reductions in mean juvenile population body size were cumulative when chronic exposures were initiated at parental reproductive maturity. Purified CBD was slightly more toxic than matched concentrations of CBD in hemp extract for all tested endpoints, and both were more toxic to juveniles than to adults. Dosimetry indicated that all adverse effect levels observed in C. elegans far exceeded recommended CBD dosages for humans.